BADANIA KLINICZNE I DOŚWIADCZALNE W CHOROBACH SERCA, PŁUC I NACZYŃOsteoprotegerin as a possible novel predictor of cardiovascular dysfunction - Stępień, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Osteoprotegerin (OPG) is a prime regulator of bone remodelling under both physiological and pathological conditions. Its role is strictly related to the receptor activator of nuclear-factor (NF)-κB ligand (RANKL), which is also produced by osteoblasts. RANKL is a main activator of osteoclasts’ differentiation during bone resorption, and OPG is a decoy receptor for RANKL, which inhibits osteoclast differentiation by interrupting interactions between RANKL and its receptor (RANK). OPG is produced by osteoclasts as well as by stromal, haematopoietic (megakaryocytes) or endothelial cells. Lymphocyte-derived cytokines also play a critical role during bone metabolism and OPG-regulated immunological stimulation. IL-4 and IL-13, T helper 2 (Th2) cytokines produced by antigen-activated T cells induce OPG production by osteoblasts. The RANK/RANKL system is also implicated in dendritic cell-T lymphocyte interactions. Thus, dendritic cell survival, T lymphocyte activation, as well as B lymphocyte development, maturation and function are regulated by OPG. On the other hand, some clinical data indicate that OPG levels are strong and independent predictors of cardiovascular disease (coronary artery calcification and hypertension), which suggests that OPG may play a regulatory role in cardiac pathology and vascular remodelling. In this article, the current view of the role of OPG as a new biomarker or prognostic parameter in cardiovascular disease will be presented.